Linear complexity of two classes of optimal sets frequency-hopping sequences - Jun-tao GAO; Yu-pu HU; Xue-lian LI; Shang-rong XIANG (Tongxin xuebao)
By using a type of permutation polynomials which were different from power permutations,the two classes of frequency-hopping sequence sets with low linear complexity was transformed into the ones with high linear complexity.The exact values of linear complexity of these sequences were given by applying the theoretical proof.The results show that the two new classes of frequency-hopping sequences sets not only have optimal Hamming correlation,but also have larger linear span and can resist the Berlekamp-Massey attack compared with the two primary classes of frequency-hopping sequence sets.